Agriculture Water Management Solutions - Ag Water Solutions, Inc.; International Food Policy Research Institute (Ag Water Solutions, Inc., 2012)
The Agricultural Water Management Solutions Project (AWM Solutions) has identified a variety of small-holder agricultural water management interventions (AWM Regional Mapping) that have a high potential to improve food security and livelihoods of the rural poor in sub-Saharan Africaand South Asia.The analysis underlying the scenarios is based on an integrated modeling system that combines geographic (GIS) data analysis, biophysical and economic predictive modeling, and crop mix optimization tools to assess the regional potential for smallholder agricultural water management across sub-Saharan Africa and South Asia. An ex-ante GIS analysis uses a set of suitability criteria to identify areas where the technology could potentially be applied, pixel by pixel, across the region based on environmental suitability and labor availability. The results are then further refined through the application of two biophysical and economic predictive modeling tools: the Soil and Water Assessment Tool (SWAT) and the model of Dynamic Research Evaluation for Management (DREAM) for a combined agronomic-economic-hydrologic cost-benefit analysis for each crop and technology assessed. Given limited market access in much of sub-Saharan Africa, we simulate local, national and international crop markets for this region, for vegetable, root and cereal crops, respectively.